The Effect of Organizational Citizenship Behavior (OCB) on Job Satisfaction in Bulukunyi Health Center and Bontokassi Health Center Employees of Takalar Regency - Badriani Badaruddin; Muhammad Khidri Alwi; Sumiaty Sumiaty; Andi Muhammad Multazam; Yusriani Yusriani; Reza Aril Ahri (Sean Institute, 2023)
Participants in this research were all temporary staff members working at either the Bulukunyi Health Center or the Bontokassi Health Center in the Takalar Regency. Analysis of the data using the technique of partial least squares (PLS). The majority of interviewees are female, have worked for less than five years, and have a college degree. There is a substantial favorable influence of Organizational Citizenship Behavior (OCB) on Job Satisfaction in both of the Puskesmas (p = 0.000). The results of this study lead us to the conclusion that employees working at the Bulukunyi Health Center and the Bontokassi Health Center in Takalar Regency are affected by the organizational citizenship behavior, also known as OCB..